2013
DOI: 10.1111/nure.12000
|View full text |Cite
|
Sign up to set email alerts
|

Effects of front-of-package and shelf nutrition labeling systems on consumers

Abstract: As standards are considered for nutrition front-of-package (FOP) and shelf-labeling systems in the United States, it is important to know what types of systems are most effective in conveying scientifically accurate and useful information to consumers. A systematic literature review identified 38 empirical studies on consumer response to FOP nutrition labeling and shelf labeling. Studies indicate that consumers can more easily interpret and select healthier products with nutrient-specific FOP nutrition labels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
327
0
25

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(376 citation statements)
references
References 36 publications
(311 reference statements)
24
327
0
25
Order By: Relevance
“…Such knowledge could provide insights into biologic pathways and could strengthen evidence available from food patterns. Furthermore, nutrition front-of-package labeling, shelflabeling, and nutrition information on restaurant menus are increasingly used by consumers to make healthier food choices [14]. It is thus also important to provide evidence on which combinations of nutrients best prevent weight gain.…”
Section: Introductionmentioning
confidence: 99%
“…Such knowledge could provide insights into biologic pathways and could strengthen evidence available from food patterns. Furthermore, nutrition front-of-package labeling, shelflabeling, and nutrition information on restaurant menus are increasingly used by consumers to make healthier food choices [14]. It is thus also important to provide evidence on which combinations of nutrients best prevent weight gain.…”
Section: Introductionmentioning
confidence: 99%
“…Standard attributes used in market research on product labelling were used in the survey. The surveys were conducted in English and French and took place August [16][17][18][19][20][21]2011. The results were weighted by age, region and gender according to Statistics Canada 2006 Census data.…”
Section: Methodsmentioning
confidence: 99%
“…A recent review indicated that people were able to more easily select a healthier product if the FOP system is nutrient-specific rather than a summary symbol. 16 Although Hersey and colleagues also noted that text plus colour was more effective than text alone when identifying healthfulness of a food, 16 our study indicated that the Traffic Light system tended to decrease the perceived healthiness of foods that are part of the four food groups in Eating Well with Canada's Food Guidelarge egg, All-Bran ® cereal, raw almonds, mild cheddar cheese and salmon -while increasing the perceived healthiness of foods that are not part of the four food groups, such as sugar-free Jello ® , fruit punch and diet soda. This is an indication of the difficulty in using these systems which are dependent on different nutrients to calculate the value and/or symbol, and how the systems can influence peoples' perceptions in very different, even conflicting, ways.…”
Section: Consumer Perceptions Of Front-of-package Labellingmentioning
confidence: 99%
“…Extensive research into the impact of food labelling across the EU has shown that many consumers can effectively use a nutrition label to rank a food for healthiness (19,23) . In addition, consistency and simplicity have modest but meaningful effects on facilitating consumer attention to the label, for example the addition of a FoP label or health logo (24)(25)(26)(27) . Consumers rate their use of nutrition labels as high; across the EU for example, up to 60 % of consumers indicate regular use of nutrient information on a food label.…”
Section: Observational Datamentioning
confidence: 99%